Martial Arts as Heritage of Mankind - Cynarski, Wojciech J. (International Martial Arts and Culture Journal, 2025)
Background and Aim. Martial arts are part of intangible cultural heritage, embodying identity values, ethics, and social practices across generations. In the modern context, martial arts are undergoing transformation through institutionalization and formalization, potentially influencing how they are practiced and interpreted. This study aims to analyze martial arts as a human heritage through an examination of their actual practice in a contemporary context.Methods. This study used a descriptive-analytical approach with an observational design. Data were obtained through systematic analysis of recordings of martial arts practice matches. The analysis focused on the characteristics of activities, technical patterns, and forms of practice that emerge as representations of martial arts in a modern context.Results. The analysis shows that martial arts practice in formal contexts is dominated by core techniques that are safe and controlled. These practice patterns reflect the martial arts' adaptation to modern demands without losing fundamental values ​​such as discipline, self-control, and precision.Conclusion. This research confirms that martial arts, as a human heritage, are dynamic and maintained through practices that remain vibrant and relevant to contemporary social contexts. Understanding actual practices is key to designing sustainable martial arts preservation strategies.